2016
DOI: 10.4049/jimmunol.1500931
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin D3 Suppresses Pulmonary Immunopathology Associated with Late-Stage Tuberculosis in C3HeB/FeJ Mice

Abstract: Tuberculosis (TB) is a significant human disease caused by inhalation of Mycobacterium tuberculosis (Mtb). Left untreated, TB mortality is associated with a failure to resolve pulmonary immunopathology. There is currently widespread interest in using Vitamin D3 (VitD3) as an adjunct therapy for TB, as numerous in vitro studies have shown that VitD3 has direct and indirect mycobactericidal activities. However, to date there have been no in vivo studies addressing whether VitD3 affects experimental TB outcome. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…A 79 nmol L −1 (31.6 ng mL −1 ) increase in serum 25(OH)D was seen amongst participants in the intervention arm of the study, which was associated with a trend towards faster sputum culture conversion ( P = 0.14) and accelerated resolution of inflammatory responses in peripheral blood . This finding was echoed by a subsequent study conducted in mice . A subgroup analysis revealed that adjunctive vitamin D significantly hastened sputum culture conversion by more than 17 days in participants with the tt genotype of the TaqI VDR polymorphism (hazard ratio 8.09, 95% CI 1.36–48.01; P = 0.02) , indicating that immunomodulatory effects of vitamin D supplementation are dependent on VDR genotype.…”
Section: Randomized Controlled Trials Investigating the Effects Of VImentioning
confidence: 91%
“…A 79 nmol L −1 (31.6 ng mL −1 ) increase in serum 25(OH)D was seen amongst participants in the intervention arm of the study, which was associated with a trend towards faster sputum culture conversion ( P = 0.14) and accelerated resolution of inflammatory responses in peripheral blood . This finding was echoed by a subsequent study conducted in mice . A subgroup analysis revealed that adjunctive vitamin D significantly hastened sputum culture conversion by more than 17 days in participants with the tt genotype of the TaqI VDR polymorphism (hazard ratio 8.09, 95% CI 1.36–48.01; P = 0.02) , indicating that immunomodulatory effects of vitamin D supplementation are dependent on VDR genotype.…”
Section: Randomized Controlled Trials Investigating the Effects Of VImentioning
confidence: 91%
“…S7 and S9) also implicated the expression of the Tlr8 pathway connected to vitamin D signaling as being strongly affected in the tlr2 mutant. Vitamin D has been shown to be an important regulatory factor during tuberculosis [72] and has been linked previously to TLR2 function in studies in cell cultures [73]. Therefore, aberrant vitamin D signaling could be a major contributing factor to the hyper-susceptibility phenotype of tlr2 mutants in Mm infection.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated polymorphism of the vitamin D binding protein to be protective in people to blastomycosis . A recent study found that oral vitamin D supplementation in M. tuberculosis ‐infected mice did not decrease the bacterial load but rather was beneficial in decreasing TB‐associated immunopathology …”
Section: Discussionmentioning
confidence: 99%